Managing Director's Global Policy Agenda. (Policy Papers; Policy Paper ;, 2013)
The global economy has avoided the worst, but it is by no means out of the woods, and prospects may be diverging. A three-speed global recovery is emerging. Sentiment has improved, but growth and jobs are still lagging in many places, some old risks remain and could rekindle tail risks, and new risks are arising. Policymakers must, to varying degrees, continue to nurse the recovery, repair systems damaged by the crisis, strengthen defenses against a recurrence, and anticipate new challenges from stronger expansion. In a world of interconnections, lagging policy momentum in some corners will soon affect all.